2017
DOI: 10.1186/s12888-017-1211-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the validity of the ICECAP-A capability measure for adults with depression

Abstract: BackgroundEffectiveness and cost-effectiveness are increasingly important considerations in determining which mental health services are funded. Questions have been raised concerning the validity of generic health status instruments used in economic evaluation for assessing mental health problems such as depression; measuring capability wellbeing offers a possible alternative. The aim of this study is to assess the validity of the ICECAP-A capability instrument for individuals with depression.MethodsHypotheses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 61 publications
8
62
1
Order By: Relevance
“…The overall ndings are consistent with previous studies that found the ICECAP-A to be promising in terms of validity [16,17,27] and responsiveness [16,28] in different populations and health conditions. The most comparable is the study by Al-Janabi et al [17], where the ICECAP-A was found to be associated with various socioeconomic variables, the EQ-5D, and questions concerning freedom and opportunities.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The overall ndings are consistent with previous studies that found the ICECAP-A to be promising in terms of validity [16,17,27] and responsiveness [16,28] in different populations and health conditions. The most comparable is the study by Al-Janabi et al [17], where the ICECAP-A was found to be associated with various socioeconomic variables, the EQ-5D, and questions concerning freedom and opportunities.…”
Section: Discussionsupporting
confidence: 91%
“…ICECAP-A is still a relatively new questionnaire, and so developing a better understanding of the tool's validity and responsiveness across populations is essential for its further use in health economic evaluations. Previous studies have demonstrated construct validity in different populations, including the general British population [17], women with irritable lower urinary tract symptoms [16] and a population with depression [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The slightly different results of the current study con rm previously identi ed weaknesses of the EQ-5D-5L instrument to measure HRQoL in severely ill mental health patients (52). Our results also con rm the ndings of a study comparing ICECAP-A and EQ-5D-5L instruments in the area of depression, which concluded that instruments designed speci cally to measure depression and mental health explained a greater proportion of the variation in ICECAP-A than the EQ-5D-5L (53).…”
Section: Discussionsupporting
confidence: 89%
“…Davis et al [35] and Couzner et al [36] reported that the difference in values between the patient and general population groups was found to be far more pronounced for the EQ-5D-3L than for the ICECAP-O. There is a consensus in the literature that changes related to the broader meaning of health are better captured by the capability instruments than by EQ-5D [37][38][39]. Coast et al [40] found strong evidence of association of general health with all capability attributes except for the attachment domain of ICECAP-A.…”
Section: Validation Of Capability Instrumentsmentioning
confidence: 99%